1981
DOI: 10.1111/j.1365-2133.1981.tb00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial mandibuloacral dysplasia

Abstract: A family is described in which two sisters and their two female fifth-cousins were cases of mandibuloacral dysplasia. This syndrome is characterized by mandibular hypoplasia, delayed cranial suture closure, dysplastic clavicles, abbreviated terminal club-shaped phalanges associated with acroosteolysis and atrophy of the skin over hands and feet. Furthermore, in this family alopecia and loss of the lower teeth were noted. We stress the importance of the cutaneous alterations and the possible existence of partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…To the best of our knowledge, only 11 families, in five of which there was one affected sib, have been reported [Schrander‐Strumpel et al, 1992]. Consanguinity was found only in one previous report [Zina et al, 1981] and in the present family, in which parents were third cousins once removed. Our patient displayed most of the MAD‐distinguishing features, whereas tissue calcifications, hypogonadism, and abnormalities of glucose metabolism [Cutler et al, 1991] were not found.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…To the best of our knowledge, only 11 families, in five of which there was one affected sib, have been reported [Schrander‐Strumpel et al, 1992]. Consanguinity was found only in one previous report [Zina et al, 1981] and in the present family, in which parents were third cousins once removed. Our patient displayed most of the MAD‐distinguishing features, whereas tissue calcifications, hypogonadism, and abnormalities of glucose metabolism [Cutler et al, 1991] were not found.…”
Section: Discussionmentioning
confidence: 47%
“…Five of the 11 reported families were of Italian origin, suggesting a common ancestor(s) [Tenconi et al, 1986]. However, consanguinity was proved only in one of these families [Zina et al, 1981].…”
Section: Introductionmentioning
confidence: 99%
“…In the familial cases, milder stigmata were seen, sometimes identified only after diagnosis of MAD in a sib [Zina et al, 19811. Inheritance undoubtedly is autosomal recessive; recurrences have been reported in male and female sibs. Consanguinity has never been documented but was suspected in 2 families [Zina et al, 1981;Tenconi et al, 19861. Two women have reproduced: they had normal children, although one of them had experienced 5 spontaneous abortions [Zina et al, 1981;Welsh, 19751. In 3 boys, puberty was noted to be delayed [case 2, Young et al, 1971;Cohen et al, 1973; Palotta andMorgese, 19841.…”
Section: Discussionmentioning
confidence: 99%
“…2,7-10 Only two out of the eleven previously reported families with MAD were determined to be consanguineous. 2,3 We believe that this case, where the parents of the patient were first-degree cousins, will add to the data on consanguinity. However, since consanguineous marriages in Turkey have a relatively high incidence, 11 the association may be considered coincidental.…”
Section: Discussionmentioning
confidence: 89%
“…The main features of the syndrome are known as delayed cranial suture closure, mandibular hypoplasia, dental crowding, hypoplastic clavicles, stiff joints, atrophy of the skin over the hands and feet, short stature, progeroid facial appearance, alopecia and acroosteolysis. [2][3][4][5] To our knowledge, there are only 25 reported cases and the majority of these are of Italian origin. 2,6 Here, we report the important case of the first Turkish patient with MAD who displayed the most severe maxillofacial and dental abnormalities known to date and who underwent therapy for the developmental orofacial morbidity.…”
mentioning
confidence: 83%